Levofloxacin-Proliposomes: Opportunities for Use in Lung Tuberculosis - Teerapol Srichana; Niracha Yanyium; Ekawat Thawithong; Titpawan Nakpheng; Wipaporn Rojanarat (MDPI AG, 2012)
Levofloxacin (LEV) is a relatively new-generation fluoroquinolone antibiotic that has good activity against Mycobacterium tuberculosis. The aims of this study were to develop and evaluate LEV-proliposomes in a dry powder aerosol form for pulmonary delivery. LEV-proliposomes containing LEV, soybean phosphatidylcholine, cholesterol and porous mannitol were prepared by a spray drying technique. The physicochemical properties of LEV-proliposomes were determined using a cascade impactor, X-ray diffraction (XRD), differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FT-IR). The toxicity of proliposomes to respiratory-associated cell lines and its potential to provoke immunological responses from alveolar macrophages (AMs) were evaluated. Antimycobacterial activity using flow cytometry and an in vivo repeated dose toxicity test in rats were carried out. LEV-proliposomes were successfully prepared with mass median aerodynamic diameters of 4.15-4.44 μm and with fine particle fractions (aerosolized particles of less than 4.4 µm) of 13%-38% at 60 L/min. LEV-proliposomes were less toxic to respiratory-associated cells than LEV, and did not activate AMs to produce inflammatory mediators that included interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and nitric oxide. The minimum inhibitory concentration (MIC) against M. bovis of LEV and LEV-proliposomes containing LEV 10% were 1 and 0.5 µg/mL, respectively. The efficacy of LEV-proliposomes against M. bovis was significantly higher than that of free LEV (p < 0.05). The efficacy of the LEV-proliposomes against M. tuberculosis was equal to that of the free LEV (MIC = 0.195 µg/mL). In a repeated dose toxicity study in rats, renal and liver toxicity was not observed. LEV-proliposomes should now be tested as an alternative formulation for delivering LEV to the lower airways.